Using AI in Healthcare: Improving Fraud Detection and Combining Petroleum and Herbal Medicine Insights - Muhammad Ibrar; Muhammad Fahad; Muhammad Umer Qayyum; Ali Husnain (CV. Multi Kreasi Media, 2024)
Artificial Intelligence (AI) is revolutionizing multiple sectors by enhancing efficiency, optimizing processes, and driving innovation. This article explores the transformative impact of AI across four diverse fields: healthcare, herbal medicine, the petroleum sector, and their interdisciplinary synergies. In healthcare, AI's applications include advanced diagnostics, personalized treatment, and improved fraud detection. Insights from the petroleum industry, where AI is used for predictive maintenance, exploration optimization, and safety management, offer valuable strategies for enhancing healthcare operations and fraud detection. Additionally, the integration of AI with herbal medicine promises to validate traditional remedies and personalize patient care by combining modern technology with ancient practices. The article highlights how cross-industry insights can lead to novel solutions and enhanced outcomes across different domains. By examining these interdisciplinary connections, the article underscores the potential of AI to bridge gaps, drive innovation, and create a more integrated approach to solving complex challenges, ultimately benefiting society and advancing the frontiers of technology and knowledge.